BANKRUPTCY JURISDICTION IN ECONOMIC JUDICIAL PROCEEDINGS - Козирєва, Валентина Петрівна; Гаврилішин, Анатолій Петрович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2020)
Purpose: general theoretical issues of definition and application of the institution of jurisdiction by commercial courts of Ukraine in bankruptcy cases are considered; the peculiarities of the activity of a commercial court in bankruptcy cases have been outlined; decrees of the Supreme Court of Ukraine have been analyzed to establish the jurisdiction. Methods: the research has been conducted using such methods as analysis, synthesis, comparative-legal knowledge of jurisdiction in commercial litigation, generalization and modeling of new theoretical knowledge. Results: it has been concluded that subjects of appeal against the actions or inaction of a state executor or other official of the body of the state executive service or a private executor may be persons who are not parties to the enforcement proceedings. In such cases, the consideration of complaints should be referred to the administrative jurisdiction of the court. It has been determined that judicial jurisdiction in accordance with the subject composition and taking into account the requirements of the law is exercised in order to ensure legality, legal certainty and access to justice. Discussion: application of jurisdiction rules considering bankruptcy cases by commercial courts of Ukraine issues. Issues of commercial courts jurisdiction in disputes are increasingly considered both at the theoretical level and in judicial practice, especially regarding the delimitation of cases between courts of general jurisdiction. The issue of bankruptcy cases jurisdiction is conflicting and insufficiently studied at the theoretical level, as there are no clear requirements for certain categories of legal disputes regarding their jurisdiction. Scholars view jurisdiction as litigation, jurisdiction, position in the hierarchy, as a set of powers of the relevant state bodies to resolve legal disputes and cases of offences and apply legal sanctions, as the competence of judicial bodies to consider civil, criminal, and other cases and the range of issues related to states. The delimitation of the powers of the courts under their jurisdiction is not only of organizational importance for the construction of the court system but also practical for sides in the respective cases. First of all, the violation of jurisdiction affects the implementation of a person’s right to judicial protection because the court to which he/she appealed refuses to consider and resolve his/her claims, and therefore his/her protection is not provided. However, it is not only the plaintiff who may make a mistake concerning the jurisdiction. The same mistake may be made by a court, which may erroneously refuse to open proceedings or close proceedings in a case falling within its jurisdiction, or erroneously consider and decide a case in which it has no jurisdiction. In all cases, the mistake from the side of the court is negative for the sides, especially for the plaintiff in case of erroneous refusal to open, close the proceedings because in such a case the plaintiff’s right to access justice is limited, and in case of erroneous consideration of the case the court decision of the first appellate court and in some cases the court of cassation may be revoked. In these cases, the plaintiff will have to seek judicial protection a second time, but in another court and start all over again. Obviously, this does not meet the interests of the plaintiff and does not contribute to the implementation of the tasks of the judiciary.